Offspring Reports on Parental Place of Upbringing: Is It Valid?. Issue 3 (May 2019) - Timm, Signe; Schlünssen, Vivi; Benediktsdottir, Bryndis; Bertelsen, Randi Jacobsen; Bråbäck, Lennart; Holm, Mathias; Jogi, Rain; Malinovschi, Andrei; Svanes, Cecilie; Frydenberg, Morten
Abstract : Supplemental Digital Content is available in the text.